2022
DOI: 10.3390/jcdd9050158
|View full text |Cite
|
Sign up to set email alerts
|

Practical Approaches to Build and Sustain a Cardio-Oncology Clinic

Abstract: The therapeutical advances in recent years in the field of oncology treatment have increased survival rates and improved the quality of life of oncology patients, thus turning cancer into a chronic disease. However, most of the new cancer treatments come at the expense of serious cardiovascular adverse events threatening the success story of these patients. The establishment of multidisciplinary medical teams to prevent, monitor, and treat cardiovascular diseases in cancer-treated patients is needed now more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…At the same time, numerous studies have demonstrated various side effects caused by chemotherapy and radiation therapy, among which cardiotoxicity has the most significant prognostic value [2,3]. Clinical manifestations of antitumor therapies' cardiotoxicity vary widely from asymptomatic subclinical changes recorded only by special imaging techniques such as global longitudinal strain measurement (GLS) and 3D-Echocardiography (EchoCG) to severe clinical symptoms evidencing heart failure and requiring emergency hospital admission [4]. Cardiotoxicity, or, according to the current definition, cancer treatment-related cardiovascular disease (CTRCD), can develop both during antitumor therapy and in the first year or even years after chemotherapy completion [5].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, numerous studies have demonstrated various side effects caused by chemotherapy and radiation therapy, among which cardiotoxicity has the most significant prognostic value [2,3]. Clinical manifestations of antitumor therapies' cardiotoxicity vary widely from asymptomatic subclinical changes recorded only by special imaging techniques such as global longitudinal strain measurement (GLS) and 3D-Echocardiography (EchoCG) to severe clinical symptoms evidencing heart failure and requiring emergency hospital admission [4]. Cardiotoxicity, or, according to the current definition, cancer treatment-related cardiovascular disease (CTRCD), can develop both during antitumor therapy and in the first year or even years after chemotherapy completion [5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is an unmet need for development and implementation of cardio-oncology programs, in order to surveil and manage cardiovascular complications before, during, and years after treatment in cancer patients. The smooth operation of such programs requires the close collaboration of health care professionals from different specialties such as oncology, cardiology, and hematology [ 6 , 7 ]. In this regard, Čiburienė et al reported the 6-year experience of the first cardio-oncology service in Vilnius, Lithuania [ 8 ].…”
mentioning
confidence: 99%